2016
DOI: 10.1007/s12098-016-2178-z
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Severity of Acute Kidney Injury in Term Neonates with Perinatal Asphyxia Using Urinary Neutrophil Gelatinase Associated Lipocalin

Abstract: Urinary NGAL is a useful biomarker for predicting AKI and its severity among neonates with perinatal asphyxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The included studies covered various backgrounds of AKI. Among them, 15 studies reported AKI occurred after CPB surgery ( 11 , 19 , 21 , 24 , 33 , 36 , 40 , 42 , 46 , 50 , 53 , 56 , 58 , 65 , 66 ), 12 studies reported AKI occurred in asphyxiated neonates ( 22 , 28 , 30 , 31 , 35 , 37 39 , 47 , 51 , 54 , 57 ), and the remaining 26 studies reported AKI occurred in children hospitalized for a variety of diseases, including sepsis, burns, solid tumors, post-liver transplantation, nephrotoxic drug use, imaging, and preterm, neonatal congenital heart disease, neonatal Hyperbilirubinemia, neonatal general surgery, etc. The diagnostic criteria for AKI used in the original studies varied and were mainly divided into the following three: pediatric risk, injury, failure, loss, final and end stage (PRIFLE) ( 67 ), Acute Kidney Injury Network (AKIN) ( 68 ) and Kidney Disease: Improving Global Outcomes (KDIGO) ( 69 ).…”
Section: Resultsmentioning
confidence: 99%
“…The included studies covered various backgrounds of AKI. Among them, 15 studies reported AKI occurred after CPB surgery ( 11 , 19 , 21 , 24 , 33 , 36 , 40 , 42 , 46 , 50 , 53 , 56 , 58 , 65 , 66 ), 12 studies reported AKI occurred in asphyxiated neonates ( 22 , 28 , 30 , 31 , 35 , 37 39 , 47 , 51 , 54 , 57 ), and the remaining 26 studies reported AKI occurred in children hospitalized for a variety of diseases, including sepsis, burns, solid tumors, post-liver transplantation, nephrotoxic drug use, imaging, and preterm, neonatal congenital heart disease, neonatal Hyperbilirubinemia, neonatal general surgery, etc. The diagnostic criteria for AKI used in the original studies varied and were mainly divided into the following three: pediatric risk, injury, failure, loss, final and end stage (PRIFLE) ( 67 ), Acute Kidney Injury Network (AKIN) ( 68 ) and Kidney Disease: Improving Global Outcomes (KDIGO) ( 69 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported a broad range of incidence of AKI after PNA, with rates as high as 55% to as low as 18.5% in neonates with PNA. [14][15][16][17][18] The AKI incidence rate was comparable to the earlier study by Zhang et al and Oncel et al 16,18 On the other hand, the rate of the present study was lesser than that observed by Tanigasalam et al and Abdelhady et al and higher than that observed by Tanzil et al and Essajee et al 16,15,17,14 Other than the small sample sizes, the variation may be due to variable definition of AKI across studies as well as the variation of the severity of PNA in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Though this was in agreement with other similar studies conducted in different countries, the uNGAL values differ significantly. [14][15][16][17][18] Further studies are essential to explain such variation in the uNGAL level among studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation